Key paediatric messages from the 2017 European Respiratory Society International Congress - KARADAĞ, BÜLENT TANER (EUROPEAN RESPIRATORY SOC JOURNALS LTD, 2018)
In this article, the group chairs of the Paediatric Assembly of the European Respiratory Society (ERS) highlight some of the most interesting findings presented at the 2017 ERS International Congress, which was held in Milan, Italy.
Keywords: LUNG CLEARANCE INDEX; MONITORING ASTHMA; PASSIVE SMOKING; CHILDREN; MANAGEMENT; DISEASE; WHEEZE